Treatment with enalapril and not diltiazem ameliorated progression of chronic kidney disease in rats, and normalized renal AT1 receptor expression as measured with PET imaging. - Basma Ismail (PLoS ONE, 2017)
ACE inhibitors are considered first line of treatment in patients with many forms of chronic kidney disease (CKD). Other antihypertensives such as calcium channel blockers achieve similar therapeutic effectiveness in attenuating hypertension-related renal damage progression. Our objective was to explore the value of positron emission tomography (PET) imaging of renal AT1 receptor (AT1R) to guide therapy in the 5/6 subtotal-nephrectomy (Nx) rat model of CKD. Ten weeks after Nx, Sprague-Dawley rats were administered 10mg/kg/d enalapril (NxE), 30mg/kg/d diltiazem (NxD) or left untreated (Nx) for an additional 8-10 weeks. Kidney AT1R expression was assessed using in vivo [18F]fluoropyridine-losartan PET and in vitro autoradiography. Compared to shams, Nx rats exhibited higher systolic blood pressure that was reduced by both enalapril and diltiazem. At 18-20 weeks, plasma creatinine and albuminuria were significantly increased in Nx, reduced to sham levels in NxE, but enhanced in NxD rats. Enalapril treatment decreased kidney angiotensin II whereas diltiazem induced significant elevations in plasma and kidney levels. Reduced PET renal AT1R levels in Nx were normalized by enalapril but not diltiazem, and results were supported by autoradiography. Reduction of renal blood flow in Nx was restored by enalapril, while no difference was observed in myocardial blood flow amongst groups. Enhanced left ventricle mass in Nx was not reversed by enalapril but was augmented with diltiazem. Stroke volume was diminished in untreated Nx compared to shams and restored with both therapies. [18F]Fluoropyridine-Losartan PET allowed in vivo quantification of kidney AT1R changes associated with progression of CKD and with various pharmacotherapies.